Molecular profile of 5-fluorouracil pathway genes in colorectal carcinoma. Issue 1 (December 2016) - Kunicka, T.; Prochazka, P.; Krus, I.; Bendova, P.; Protivova, M.; Susova, S.; Hlavac, V.; Liska, V.; Novak, P.; Schneiderova, M.; Pitule, P.; Bruha, J.; et al.
Abstract Background This study addresses involvement of major 5-fluorouracil (5-FU) pathway genes in the prognosis of colorectal carcinoma patients. Methods Testing set and two validation sets comprising paired tumor and adjacent mucosa tissue samples from 151 patients were used for transcript profiling of 15 5-FU pathway genes by quantitative real-time PCR and DNA methylation profiling by high resolution melting analysis. Intratumoral molecular profiles were correlated with clinical data of patients. Protein levels of two most relevant candidate markers were assessed by immunoblotting. Results Downregulation of DPYD and upregulation of PPAT, UMPS, RRM2, and SLC29A1 transcripts were found in tumors compared to adjacent mucosa in testing and validation sets of patients. Low RRM2 transcript level significantly associated with poor response to the first-line palliative 5-FU-based chemotherapy in the testing set and with poor disease-free interval of patients in the validation set irrespective of 5-FU treatment.UPP2 was strongly methylated while its transcript absent in both tumors and adjacent mucosa.DPYS methylation level was significantly higher in tumor tissues compared to adjacent mucosa samples. Low intratumoral level ofUPB1 methylation was prognostic for poor disease-free interval of the patients (P  = 0.0002). The rest of the studied 5-FU genes were not methylated in tumors or adjacent mucosa. Conclusions The observed overexpression of several 5-FU activating genes and DPYD downregulation deduce that chemotherapy naïve colorectal tumors share favorable gene expression profile for 5-FU therapy. Low RRM2 transcript andUPB1 methylation levels present separate poor prognosis factors for colorectal carcinoma patients and should be further investigated.